Completion imaging techniques and their clinical role after carotid endarterectomy: Systematic review of the literature. (December 2020) - Spanos, Konstantinos; Nana, Petroula; Kouvelos, George; Batzalexis, Konstantinos; Matsagkas, Miltiadis M; Giannoukas, Athanasios D
Background: Completion imaging has been suggested for the intraoperative quality control assessment of the carotid endarterectomy technical success, in order to immediately resolve pathologic findings and accordingly improve patients' outcome. The aim of this study was to present existing evidence of different completion imaging techniques after carotid endarterectomy and their role on clinical outcome. Material and methods: A systematic review was performed searching in MEDLINE, CENTRAL, and Cochrane databases including studies reporting on completion imaging techniques after carotid endarterectomy. Results: A total of 12, 378 patients in 35 studies (20 retrospective and 15 prospective) underwent a completion imaging technique after carotid endarterectomy: in 19 studies, 5340 patients underwent arteriography; in 5 studies, 2095 angioscopy; in 21 studies, 5722 DUS; and in 2 studies, 150 patients underwent transcranial Doppler. Ten studies assessed > 1 imaging technique. The mean age was 67 ± 7 years old (69% males) with common co-morbidities to be hypertension (74%), smoking (64%), and hyperlipidemia (54%). Almost half of the patients (4949; 44%) were treated for symptomatic disease. In 1104 (9.7%) patients, a major defect was identified intra-operatively, while in 329 patients (2.9%), a minor defect. Common pathological findings were the presence of mural thrombus, carotid dissection, residual stenosis, and intimal flaps. An immediate re-intervention was undertaken in 75% (790/1053) of the patients to treat a major intra-operative imaging finding. In patients with re-intervention, only 2.3% (14/609) had an intra-operative stroke and 0.8% (5/609), a transient ischemic attack, while only 1.4% (8/575) had a stroke and 0.2% a transient ischemic attack (1/575) during 30-day post-operative period. No intra-operative death was reported. In the same period, the restenosis rate of internal and common carotid artery was 0.5% (3/575) and 0.2% (1/575), respectively. Conclusion: Completion imaging techniques can detect defects in almost 10% of patients that may lead to immediate intra-operative surgical revision with low intra-operative stroke/transient ischemic attack rate and low early carotid restenosis. During the 30-day follow-up period, in those patients, the incidence of stroke/transient ischemic attack may be low but present. This review cannot provide any evidence on which completion imaging technique is better, and the clinical impact conferred by each technique in the absence of a randomized control studies.